The Sri Ayutthaya Female Detective: The Heroine of Investigation and the Man in Shadow - Ying, Zhang; Chaiprasert, Jansuda (Academic and Research Journal of Liberal Arts (Online), 2025)
This research article analyzes the roles of supporting characters who assist the female protagonist’s transformation into the heroine in the series of historical detective novels called The Sri Ayutthaya Female Detective. The research finds two types of supportive characters, as follows. 1) The male character who expands the potential and abilities of the female protagonist. He has a higher social rank than the protagonist; holds a firm profession; and is a specialist, having more knowledge and experience than the protagonist. These characteristics increase the status and capability of the protagonist. 2) The female supporting character typically occupies a lower social or economic status than the female protagonist. Traditional gender norms do not bind her and operate beyond conventional expectations of femininity. Her personality often starkly contrasts with the protagonist's, and her role is to provide support by undertaking actions or responsibilities that the protagonist is unable or unwilling to perform. Through these supporting characters, the series reveals an underlying message that females are dependent on males. To be successful, they must overcome the social limitations imposed on them.